Factors associated with the use of combined nutritional complementary and alternative medicine among southern US older adults: results from the study of aging II - Allen-Watts, Kristen; Rumble, Deanna; Taylor, Taylor; Sims, Andrew; Antoine, Lisa H.; Logan, Georgiana; Brown, Cynthia J.; Buford, Thomas W.; Goodin, Burel R.; Cherrington, Andrea; Kennedy, Richard (Frontiers in Nutrition, 2025)
BackgroundOlder adults use nutritional complementary and alternative medicine (CAM) to reduce the risk of (or treat) non-communicable conditions and diet deficiencies. While prior research has explored the individual use of dietary supplements, vitamins, and minerals among older adults, few studies have examined factors influencing the combined use of these modalities, especially among Southern, older adults in the United States.MethodsData were extracted from 419 participants from the University of Alabama at Birmingham Study of Aging II, a population-based longitudinal study of mobility among community-dwelling older adults. Self-reported data, including insurance and rural residence status, was collected. Comorbidity burden was assessed using the Charlson Comorbidity Index. Participants reported their use of non-prescribed medications, including dietary supplements, vitamins, and minerals. Logistic regression was used to identify factors associated with the use of combined nutritional CAM modalities.ResultsWe found a statistically significant association between sex (p < 0.001), age (p = 0.024), rural living status (p = 0.008), and education (p < 0.001) in use of combined nutritional CAM (dietary supplements, vitamins, and minerals). For the use of vitamins and minerals only, our findings suggest a significant association between sex (p = 0.027), age (p < 0.001), and education (p = 0.009). Lastly, for the use of dietary supplements only, our findings suggest a significant association between age (p = 0.050) and education (p = 0.002).ConclusionOur study addresses a critical gap by examining the sociodemographic and chronic disease burden predictors of concurrent use of combined nutritional CAM modalities among older adults in the Southern United States. Such insights can help inform public health strategies and clinical guidance aimed at supporting the health and well-being of older adults, particularly as they navigate complex health decisions in the context of aging.